Association of VEGFA polymorphisms with chronic obstructive pulmonary disease in Chinese Han and Mongolian populations. Issue 8 (8th July 2021) - Gao, Xiaoyu; Wang, Xin; Jiao, Na; Chen, Jiyuan; Sun, Dejun
Abstract : New Findings: What is the central question of this study? Vascular endothelial growth factor A (VEGFA) is an important growth factor involved in changes in the bronchial microvascular and airway inflammation in chronic obstructive pulmonary disease (COPD) progression. What is the association of single nucleotide polymorphisms (SNPs) in VEGFA with the risk of COPD in the Chinese Han and Mongolian populations? What is the main finding and its importance? The effect of five SNPs in the VEGFA gene was analysed and compared between the Chinese Han and Mongolian populations. A contribution of risk alleles rs833068, rs833070 and rs3024997 to COPD was detected in the Chinese Mongolian population only. The study provided data from different populations to validate the role of VEGFA polymorphisms in COPD and provided reliable SNPs to predict the risk of COPD. Abstract: We attempted to define the associations between single nucleotide polymorphisms (SNPs) in the vascular endothelial growth factor A ( VEGFA ) gene and chronic obstructive pulmonary disease (COPD) in Chinese Han and Mongolian cohorts. Five SNPs were genotyped in cohorts of 684 COPD patients (350 Mongolian and 334 Han) and 784 healthy controls (350 Mongolian and 434 Han) using SNPscan multiplex PCR. SNP frequencies, genetic models and haplotypes were analysed using the chi‐square test. The associations of SNPs with COPD and linkage disequilibrium were analysed using logistic regression and HaploView, respectively. We found that only rs833068G>A, rs833070T>C and rs3024997G>A were significantly associated with the risk of COPD in the Mongolian population (rs833068: P  < 0.001, rs833070: P  < 0.001, rs3024997: P  = 0.002). In the analysis of genotype distributions, the A/A and G/A genotypes in rs833068 (A/A: odds ratio (OR) = 0.313, P  < 0.001; G/A: OR = 0.724, P  < 0.001) and rs3024997 (A/A: OR = 0.513, P  = 0.008; G/A: OR = 0.671, P  = 0.008) and the C/C and T/C genotypes in rs833070 (C/C: OR = 0.435, P  = 0.007; T/C: OR = 0.593, P  = 0.007) were associated with protection against COPD in the Mongolian population. The haplotype frequencies of GCCAT and GTCGC were significantly different between the patients and controls (GCCAT: P  = 0.001; GTCGC: P  < 0.001) in the Mongolian population. Our findings indicate that five SNPs in the VEGFA gene play divergent roles in the Han and Mongolian populations. rs833068A, rs833070C and rs3024997A were observed to be associated with the risk of COPD in the Mongolian population. Abstract :